Excitons versus free charges in organo-lead tri-halide perovskites. - D'Innocenzo, V; Grancini, G; Alcocer, M; Kandada, A; Stranks, S; Lee, M; Lanzani, G; Snaith, H; Petrozza, A (2014)
Excitonic solar cells, within which bound electron-hole pairs have a central role in energy harvesting, have represented a hot field of research over the last two decades due to the compelling prospect of low-cost solar energy. However, in such cells, exciton dissociation and charge collection occur with significant losses in energy, essentially due to poor charge screening. Organic-inorganic perovskites show promise for overcoming such limitations. Here, we use optical spectroscopy to estimate the exciton binding energy in the mixed-halide crystal to be in the range of 50 meV. We show that such a value is consistent with almost full ionization of the exciton population under photovoltaic cell operating conditions. However, increasing the total photoexcitation density, excitonic species become dominant, widening the perspective of this material for a host of optoelectronic applications.